Splatoon. Vol. 12 - Hinodeya, Sankichi; Turnage, Bryant (VIZ Media, LLC, 2021)
"The final chapter of the Hero Mode arc is here! Find out how it ends for Specs and the gang. And then, a brand new story brings you further into the world of Splatoon. It's time to get to know Sheldon! His adventure starts right now!"--Provided by publisher.